O atendimento educacional especializado em sala de recursos multifuncionais em um município do interior paulista - Malheiro, Cicera Aparecida Lima (2013)
Among the set of actions instituted by the federal government is the Program Implementation Meeting Resources Multifunction (PI-MRM) that aims to support the public school systems in the organization and delivery of the Educational Service Specialist (ESS) to target students in special education (SSE). Through the PI-MRM were distributing resource materials, furniture and equipment, computer systems and networks for education. The aim of this study was to describe and analyze how the guidelines of PIMRM has been translated by a municipal school system in the interior, from the organization and delivery of ESS, under three aspects: service, training and evaluation. The design based on collaborative research involved the development of a training process and investigative next twenty-five special education teachers (SET) who worked in MRM and three SET that comprised the management team of inclusive education, in a town in state of São Paulo. To operate this process, we used a systematic collaboration with the participants through four procedural steps: First Step - Characterization of the Implementation of MRM, Second Step - Survey of the descriptions of the three axes that guide this research (service, training and evaluation), Third Step - Development of training topics defendants; Fourth Step - Clash of the content and directions of Reconstruction. Os resultados indicaram que no sistema municipal participante da pesquisa: a matrícula do aluno PAEE em sala comum foi respaldada pelo apoio do AEE em SRM e foi ampliada continuamente; no decorrer da implantação do AEE em SRM, houve diferentes níveis de traduções, que foram realizados pelas PEE, junto aos demais profissionais da educação, e que resultaram na implantação do PI-SRM de forma diferenciada em cada realidade escolar. The results indicated that the municipal research participant: the enrollment of the student common room in SEE was supported by ESS in support of MRM and was expanded continuously, during the implementation of the ESS in MRM, there were different levels of translations, which were performed by SET, together with other education professionals, and which resulted in the deployment of PI-MRM differently in each school reality. The seizure of the translations of the policy with regard to PI-MRM resulted in obtaining information that showed that the translations occurred at different levels (municipal, teachers, schools) specifically when taking as parameter the propositions of PI-MRM. It was found that the documents and legal advisors comprising the municipal policy, to provide a basis despite the higher laws of the country, not contemplated in its legal apparatus PI-MRM guidelines. It was evident that the conduct of the training was also conducted for the SET. However, each has a distinct need SET, given the demands of their work and the realities of professional development that meet.